Injury careers after blast exposure among combat veterans deployed to Iraq or Afghanistan. (December 2015) - Chase, Rachel P.; McMahon, Shannon A.; Winch, Peter J.
Abstract: During the Iraq and Afghanistan wars, blasts were the most common cause of combat injuries, including traumatic brain injury (TBI). Prior to 2007, service members were not systematically screened for TBI, and estimates suggest that tens of thousands of mild TBIs went undiagnosed. This study sought to understand post-acute "injury careers, " documenting the life- and health-related narratives of veterans who were at high risk of undocumented TBI due to being blast-exposed before 2007. Researchers conducted 38 in-depth interviews between May 2013 and August 2014 with Army veterans who served in combat-intense settings ( n  = 16) and their family members ( n  = 10). Respondents detailed a series of experiences in the months and years following blast exposure. We present this series as a model that draws upon the vernacular of participants who described veterans "downplaying" their injuries and later "detaching" themselves from friends, family, and communities, and "denying" or being "oblivious" to their circumstances until a "wake-up call" pushed them to "get help." Looking to the future, veterans grapple with uncertainties related to personal identity and professional or social expectations. This model is presented within a member-checked metaphor of an individual being hurled into – and emerging from – a canyon. Policies and programs addressing veteran health, particularly among those exposed to multiple blasts prior to systematic TBI documentation, must consider the personal, social, and health system challenges faced by veterans and their families throughout their injury careers. Highlights: Examines accounts of OEF/OIF veterans exposed to blast before routine TBI screening. The study delineates a seven-phase model of veteran post-blast injury careers. Veterans downplay, are oblivious to, and deny the insidious effects of blasts. Careseeking is often preceded by a low point in the lives of veterans and their families. Veteran and family needs are under-addressed throughout the injury career.